A RAINBOW ON THE TABLE: Historical Study Of Culinary Diversity In Solo - Heri Priyatmoko (Jurnal Sosiologi Reflektif, 2020)
This research attempts to understand the history of culinary diversity in Solo as a symbol of cultural harmony, as well as a regional economic power. The purpose of this research is motivated by the fact that Solo is known as a “radical city” and a city of conflict at national level. This study is expected to give a more comprehensive understanding of portrait of ethnic harmony which is reflected in the culinary cultures in order to lessenthe negative image of Solo. The method used is historical method, including heuristics (gathering of sources), source criticism, analysis/interpretation and writing. The researcher dedicated most time and energy to do library and document research and conduct some interview with the culinary businessmen. The researcher applies the acculturation theory in order to understand the process of culinary diversity occurrence. The result shows that the diversity of culinary of Solo is created as a result of intensive inter-cultural association and is supported by the creativity of local communities in addressing a challenge that led to the creation of new types of food. The existence of Javanese, European, Chinese, and Arabic communities in the past is accounted for the diversity of food on the table, which becomes a symbol of social harmony. From tourism perspective, the character of the people who have hobby of eating out and the availability of various types of culinary strengthen the image of Solo City as “keplek ilat” (mouthwatering) city. This fact in turn becomes the economic power of Solo City.